Abdominal Pain and Vomiting. Issue 4 (December 2017) - McCambridge, Joshua; Wang, Peter
Abstract : Abstract: Abdominal ultrasound of a 28-year-old man with chronic abdominal pain and vomiting demonstrates a dilated aperistaltic distal esophagus, which was confirmed on follow-up esophagram as achalasia. The 2 main types of achalasia are primary and secondary. Primary achalasia occurs with the loss of postganglionic neurons resulting in failed distal esophageal relaxation. Secondary achalasia is esophageal narrowing due to nondenervation causes. The diagnosis of achalasia is typically made with manometry and barium esophagram. Abstract : Supplemental digital content is available in the text.